Respuesta :
Answer:
x = (-3)/4
Step-by-step explanation:
Solve for x:
3 (x - 6) = 8 x - 3 (3 x + 7)
-3 (3 x + 7) = -9 x - 21:
3 (x - 6) = 8 x + -9 x - 21
Grouping like terms, 8 x - 9 x - 21 = (8 x - 9 x) - 21:
3 (x - 6) = (8 x - 9 x) - 21
8 x - 9 x = -x:
3 (x - 6) = -x - 21
Expand out terms of the left hand side:
3 x - 18 = -x - 21
Add x to both sides:
3 x + x - 18 = (x - x) - 21
x - x = 0:
3 x + x - 18 = -21
3 x + x = 4 x:
4 x - 18 = -21
Add 18 to both sides:
4 x + (18 - 18) = 18 - 21
18 - 18 = 0:
4 x = 18 - 21
18 - 21 = -3:
4 x = -3
Divide both sides of 4 x = -3 by 4:
(4 x)/4 = (-3)/4
4/4 = 1:
Answer: x = (-3)/4
Answer:
Just solve for "x"
3(x - 6) = 8x - 3(3x + 7)
3x -18 = 8x -9x -21
4x = -3
x = -3 / 4
Step-by-step explanation: